Evaluation of Low Cost-Activated Carbon Produced from Waste Tyres Pyrolysis for Removal of 2-Chlorophenol - Kanchana Manirajah; Sheela V. Sukumaran; Nor Nasuha Abdullah; Hazirah A. Razak; Nurul Ainirazali (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
A low cost Activated Carbon (AC) was prepared by using waste tyres as raw material for the removal of 2-chlorophenol (2-CP). The AC adsorbent was prepared and activated by pyrolysis process at 900 ºC under constant nitrogen flow. The physical properties of the AC produced was characterized using X-ray Diffraction (XRD), Brunauer-Emmett-Teller (BET), Field Emission Scanning Electron Microscopy (FESEM), and Fourier Transform Infra Red (FTIR). The influence of initial adsorbate concentration, pH and adsorbent dosage on the removal of 2-CP in the batch-operational mode at ambient temperature were also investigated. The results obtained showed the AC presence of an amorphous carbon with high BET surface area and a total pore volume of 208 m2.g-1 and 0.5817 cm3, respectively. The highest adsorption capacity of 2-CP by the AC absorbent was achieved at an initial concentration of 10 mg.L-1, pH 5, and adsorbent dosage of 0.5 g in the first 10 min of contact time. This finding proves that the low cost-AC produced from waste tyres can be utilized for an effective removal of chemical plant wastewater containing toxic chlorine substances. Copyright © 2019 BCREC Group. All rights reserved